Cape Town Triennial 1985. - Rembrandt van Rijn Art Foundation; Durban Art Gallery, Durban; Johannesburg Art Gallery, Johannesburg; King Georg VI Art Gallery, Port Elizabeth; Pretoria Art Museum, Pretoria; Tatham Art Gallery, Petermaritzburg; University of the Orange Free State Art Gallery, Bloemfontein; Cape Town Triennial 1985 (Kaapstad : South African National Gallery, 1985)
Alexander, Jane ; Alice, Bonita ; Anderson, Ilona ; Armstrong, Juliet ; Arnold, Marion ; Beeton, Julia ; Bell, Deborah ; Bleach, Gordon ; Botha, Andries ; Calder, Ian ; Catherine, Norman ; Cheminais, Gaby ; Clarke, John ; Coetzee, Cyril ; Coetzee, Neels ; Crooks, Jennifer ; Crouse, Reshada ; Dietrich, Keith ; Dubow, Neville ; du Toit, Guy ; Emsley, Paul ; Ferreira, Angela ; Gavronsky, Claire ; Goedhals, Nell ; Goldberg, Michael ; Grandison, Sheila ; Hagg, Gerard ; Halsted, Fée ; Hleza, Austin ; etc.
Cape Town Triennial 1985, Tour Programme 1985/86 : SA National Gallery, Cape Town, September 18 - November 2 ; King George VI Art Gallery, Port Elizabeth, November 21 - January 15 ; University of the Orange Free State Art Gallery, Bloemfontein, January 29 - February 21 ; William Humphreys Art Gallery, Kimberley, March 12 - April 15 ; Tatham Art Gallery, Pietermaritzburg, May 7 - June 15 ; Durban Art Gallery, Durban, June 25 - August 3 ; Johannesburg Art Gallery, Johannesburg, August 18 - September 28 ; Pretoria Art Museum, Pretoria, October 8 - November 16
boek